Reduction of nitrate to ammonia using photocatalytically accumulated electrons on titanium(IV) oxide in a time-separated redox reaction - Murakami, Naoya; Suenaga, Masato; Deguchi, Ryota (Inorganic chemistry communications, 2022)
[Display omitted] •Reduction of NO3− to ammonia NH3 was performed by a time-separated redox reaction.•The reaction uses a two-step reaction under the control of photoexcitation an electron acceptor.•Eight-electron reduction of NO3− to NH3 was performed by accumulated electrons in a TiO2 suspension.•The use of a rutile sample with a large number of defective sites is a key factor for the reaction. Reduction of nitrate (NO3−) to ammonia (NH3) was performed by a time-separated redox reaction using photocatalytically accumulated electrons in a titanium(IV) oxide (TiO2) suspension. The time-separated redox reaction uses a two-step reaction under the control of photoexcitation and an electron acceptor: (1) accumulation of electrons in TiO2 powder under photoexcitation and (2) reduction of added NO3− by accumulated electrons in the dark. Color change of TiO2 depending on the degree of electron accumulation was observed during the reaction, and 8-electron reduction of NO3− to NH3 was performed by accumulated electrons. The results of the time-separated redox reaction using 10 kinds of commercial TiO2 powder indicate that the use of a rutile sample with a large number of trivalent titanium species is a key factor for NH3 production.